Who has an edge in trading index derivatives? - Jang, Jeewon; Kang, Jangkoo; Lee, Jaeram (Journal of Futures Markets, 2023)
Using the transaction data of a leading index derivatives market, we find that foreign institutional investors make huge profits while domestic individuals lose almost the same amount. Our empirical findings show that foreign institutional investors' profits cannot be attributed to their overnight information advantage or reward for liquidity provision. Our evidence is consistent with the hypothesis that foreign investors have superior marketwide information about intraday changes in the underlying index.
Keywords: foreign investors; index derivatives; information advantage; overnight information; trading profit